Propaganda, power and persuasion : from World War I to Wikileaks - Welch, David, 1950- (International library of historical studies ;, 2014)
As Philip Taylor has written, 'The challenge (of the modern information age) is to ensure that no single propaganda source gains monopoly over the information and images that shape our thoughts. If this happens, the war propagandists will be back in business again.'Propaganda came of age in the Twentieth Century. The development of mass- and multi-media offered a fertile ground for propaganda while global conflict provided the impetus needed for its growth. Propaganda has however become a portmanteau word, which can be interpreted in a number of different ways. What are the characteristic feat.